ANALISIS PENERAPAN SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK HIBURAN DI KOTA BITUNG - Ponto, Chrysti D.; Karamoy, Herman; Runtu, Treesje (Universitas Sam Ratulangi, 2015)
Regional autonomy in Indonesia came into force on 1 January 2001. Regional Government Law 28 of 2009 on Regional Tax and Retribution, is set to be one source of revenue that comes from inside the area. Bitung is one of the autonomous regions. With the availability of a variety of entertainment, receipt Pemerintahpun revenue increase due to impose a tax on organizing entertainment such entertainment. The objective of this study is to determine the application of tax collection systems and procedures of entertainment in the city of Bitung. The object of research is the Regional Revenue Office Bitung. This type of research, namely, qualitative research and analysis method used is descriptive analysis method. The results showed that the systems and procedures for the collection of entertainment tax imposed by the Regional Revenue Office Bitung as the tax authorities have been implemented properly, because in accordance with the Regional Regulation No. 1 in 2013, Mayor Regulation No. 21 in 2013, and Regulation No. 13 Year 2006. Regional Revenue Office Bitung City should continue to maintain the systems and procedures in accordance with the entertainment tax collection regulations.